Anode catalyst for resisting CO poisoning and preparation method thereof

By using doped carbon support and precious metal alloy nanoclusters in the anode catalyst, the outer oxide barrier layer and the inner layer of highly alloyed PtRu particles are formed, and the existing catalysts are solved, and the catalytic effect with high CO tolerance and low cost is achieved.

CN119812372APending Publication Date: 2025-04-11SINOCAT ENVIRONMENTAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411946682.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing anode catalysts are difficult to maintain the ability to efficiently convert H2 at high CO concentrations, and the precious metal load is high and the cost is high, which affects the large-scale application of PEMFC.

Method used

The carbon support and catalysts that support precious metals and their oxide nanoclusters are used to doplate carbon support and regulate the structure of precious metal alloys, forming an outer oxide barrier layer and an inner layer of highly alloyed PtRu particles, combining physical barriers and metal ligand effects to enhance CO tolerance.

Benefits of technology

It significantly improves the CO tolerance and catalytic efficiency of the catalyst, reduces the amount of precious metals, and reduces the purification cost of hydrogen for PEMFC, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812372A_ABST
    Figure CN119812372A_ABST
Patent Text Reader

Abstract

The invention discloses an anode catalyst for resisting CO poisoning and a preparation method thereof, and belongs to the technical field of catalysts. The anode catalyst is composed of a carbon carrier and noble metal and oxide nanoclusters thereof loaded on the carbon carrier, wherein the loading amount of the noble metal in the noble metal and oxide nanoclusters thereof is 25-75 wt% of the total loading amount of the anode catalyst; wherein the noble metals are ruthenium and platinum, and the weight ratio of ruthenium to platinum is (1-5): 1. The preparation method is used for preparing the noble metal catalyst. According to the anode catalyst disclosed by the invention, the dosage of noble metals in the catalyst components can be reduced, efficient hydroxide activity and stability can be kept, and the anode catalyst has remarkable CO poisoning resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, in particular to an anode catalyst resistant to CO poisoning and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is an energy conversion device with high energy density and high power density, and has great development potential in the future. Catalysts are its key components, and both cathode and anode catalysts face challenges, especially on the PEMFC anode catalyst layer. Hydrogen (H2) is oxidized on platinum (Pt)-based catalysts to release electrons and protons to complete the hydrogen oxidation reaction (HOR). However, the active component Pt is very sensitive to impurities in hydrogen fuel such as carbon monoxide (CO) and sulfur (S). Even trace amounts of CO (<10ppm) can cause catalyst poisoning and deactivation, thereby reducing the catalytic reaction activity. Therefore, the requirements for the impurity content of hydrogen used in PEMFC are very strict.

[0003] The hydrogen currently produced is mainly produced from coal. Although the cost is low and the technology is mature, the CO content in the gray hydrogen that has not been deeply purified far exceeds the CO content requirement for PEMFC hydrogen (0.2ppm, GB / T37244-2018). If the catalyst's tolerance to CO can be regulated so that it can still efficiently convert H2 at relatively high CO concentrations, the purification cost of PEMFC hydrogen (such as gray hydrogen) will be greatly reduced, which will be beneficial to the large-scale application of PEMFC.

[0004] There are currently two design ideas for improving the tolerance of anode catalysts to CO:

[0005] 1. Reduce the CO adsorption capacity. From the perspective of catalyst micro-design, it can be understood as weakening the bonding ability between CO and the catalyst surface and reducing the coverage of CO on the catalyst surface. There are two methods that can be adopted:

[0006] 1.1 Use physical barriers (such as carbon layer, metal oxide layer) to isolate the contact between catalyst nanoparticles and CO molecules and reduce the adsorption of impurities on the catalyst surface.

[0007] However, this method will result in a thicker barrier layer, and an excessively thick barrier layer will hinder the contact between the reactant molecules and the active sites, thereby affecting the catalytic efficiency.

[0008] 1.2 By introducing other elements such as ruthenium (Ru) and molybdenum (Mo), the electronic structure of Pt is changed, the Pt-CO bonding ability is weakened, and the CO (electro)chemical adsorption effect is weakened. This electronic effect helps to reduce the adsorption intensity of CO on the Pt surface, thereby reducing the possibility of CO poisoning.

[0009] 2. Increase the CO oxidation rate, specifically, to improve the ability to oxidize and remove CO at (low) working potential. The most classic method is to design alloy catalysts, such as binary and multi-element alloy catalysts such as Pt-Ru, Pt-Ni, Pt-Sn, Pt-WO3, and Pt-Mo, which can not only reduce the content of precious metal Pt, but also enhance the ability to resist CO poisoning through the "coordination effect" between two or more metals. Among them, PtRu is considered to be one of the best catalysts for this method because the presence of Ru can promote the oxidation reaction of CO intermediates with OH, thereby effectively converting CO into carbon dioxide (CO2). This reaction mechanism helps to convert CO on the catalyst surface and maintain the activity of the catalyst.

[0010] However, since the working potential of HOR in PEMFC is very low (usually less than 0.10 V vs RHE), the CO oxidation rate is too slow to exceed its adsorption rate; at the same time, during the CO poisoning process, the catalyst stability is also low due to the poor interaction between Ru and (or) Pt-Ru on the catalyst surface and the carrier carbon.

[0011] In summary, although there are many ideas and achievements in the design of CO2-tolerant catalysts for PEMFCs, there are still challenges in terms of stability and catalytic efficiency at high CO concentrations. Therefore, it is necessary to explore CO2-tolerant strategies that go beyond traditional methods to solve these problems.

[0012] In the current state of the art of anode catalysts, the requirement to improve CO tolerance while maintaining high performance and reducing precious metal loading (especially platinum) remains a major challenge that needs to be addressed, and attempts to reduce its loading often lead to a decrease in catalyst performance. In addition, improving CO tolerance usually requires changes to the composition, structure or surface properties of the catalyst, but these changes may affect the activity, stability and selectivity of the catalyst, thereby limiting its performance in practical applications.

[0013] At present, traditional Pt / C catalysts cannot cope with trace amounts of CO poisoning. Although PtRu / C catalysts, as a new type of CO-resistant catalyst, have made some progress, this type of catalyst still cannot meet the needs of CO-resistant fuel cells under high CO concentrations. The performance and stability in practical applications still need to be further verified and optimized. Summary of the invention

[0014] The object of the present invention is to provide an anode catalyst resistant to CO poisoning, in which the amount of precious metals in the catalyst components can be reduced, the efficient hydrogen oxidation activity and stability can be maintained, and the catalyst has significant CO tolerance. At the same time, the present invention also provides a preparation method for synthesizing the anode catalyst resistant to CO poisoning.

[0015] The first aspect of the present invention provides an anode catalyst resistant to CO poisoning, which is composed of a carbon carrier and precious metals and their oxide nanoclusters loaded on the carbon carrier, wherein the loading amount of the precious metals in the precious metals and their oxide nanoclusters is 25 to 75 wt% of the total loading amount of the anode catalyst; wherein the precious metals are ruthenium and platinum, and the weight ratio of ruthenium to platinum is 1 to 5:1.

[0016] In the anode catalyst, the carbon support is a heteroatom-doped carbon support;

[0017] The heteroatom in the heteroatom-doped carbon carrier is a nitrogen atom and / or a sulfur atom;

[0018] The total doping amount of the nitrogen atoms and / or sulfur atoms is 1.8-2.2% of the weight of the carbon carrier.

[0019] In the anode catalyst, the nanoparticle diameter of the noble metal and its oxide nanocluster is 2.5-5.0 nm.

[0020] The second aspect of the present invention provides a method for preparing an anode catalyst resistant to CO poisoning, which is used to prepare the above-mentioned anode catalyst, and comprises the following steps:

[0021] S1: 0.1-1.0 g of carbon carrier is added into the solvent and sheared for 30 min to obtain a uniformly dispersed slurry;

[0022] S2: mixing the slurry with a noble metal ruthenium precursor solution, adding 1.0-10.0 mL of an inorganic base with a concentration of 0.1-2.0 mol / L to carry out a heating reaction, and then adding a noble metal platinum precursor solution to carry out a heating reaction after cooling; wherein the content of ruthenium in the noble metal ruthenium precursor is 0.2-2.0 g, and the content of platinum in the noble metal platinum precursor is 0.1-1.0 g;

[0023] S3: cooling the slurry after the heating reaction, adding deionized water, and then adding 1.0-20.0 mL of an inorganic acid solution with a concentration of 0.1-1.5 mol / L to carry out stirring reaction; wherein the reaction temperature of the stirring reaction is 60-100° C., and the stirring time is 1.0-3.0 h;

[0024] S4: adding water to the slurry after the stirring reaction, filtering and washing, and vacuum drying, the vacuum drying temperature is 60-100° C., and the treatment time is 12.0-48.0 hours to obtain a catalyst powder;

[0025] S5: subjecting the catalyst powder to oxidation treatment to obtain the anode catalyst.

[0026] Based on the above preparation method, the carbon carrier in step S1 is prepared by the following method:

[0027] A common carbon carrier is doped with heteroatoms through gas phase assistance to obtain the carbon carrier functionalized with heteroatoms.

[0028] Based on the above preparation method, the common carbon carrier further comprises a pretreatment step, and the pretreatment step comprises:

[0029] Weigh 0.1-1.0 g of common carbon carrier, add 5.0-50 mL of inorganic acid solution, heat and stir, wash with hot water until neutral, and then vacuum dry.

[0030] In the preparation method, the common carbon carrier is one of carbon black, activated carbon, graphite carbon, carbon nanotubes, graphene, and mesoporous carbon, or a mixture of any two or more of the above substances.

[0031] Based on the above preparation method, the specific steps of the gas phase assistance are:

[0032] Place the common carbon support in a closed environment;

[0033] Passing a gas containing a nitrogen source and / or a sulfur source into a closed environment;

[0034] The common carbon carrier is heat-treated at a temperature of 300 to 600° C., wherein the heating rate of the heat treatment is 5 to 20° C. / min and the duration is 30 to 180 min.

[0035] Based on the above preparation method, in step S1, the shear rate is 8000-12000 rpm, and the solvent is any one of ethylene glycol, propylene glycol, glycerol, diethylene glycol, butylene glycol, diethylene glycol, triethylene glycol, or a mixture of any two or more thereof.

[0036] Based on the above preparation method, in step S2:

[0037] In the noble metal ruthenium precursor solution, the noble metal ruthenium precursor is one of ruthenium trichloride, ruthenium acetylacetonate, ammonium hexachlororuthenate, hydrated potassium pentachlororuthenate, or a mixture of any two or more thereof;

[0038] In the noble metal platinum precursor solution, the noble metal platinum precursor is one of chloroplatinic acid, platinum chloride, platinum nitrate, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, sodium chloroplatinite, or a mixture of any two or more thereof;

[0039] The inorganic base is one of sodium carbonate, sodium hydroxide, potassium hydroxide, potassium carbonate, or a mixture of any two or more thereof;

[0040] The heating reactions were both carried out under an inert gas atmosphere, wherein the heating temperature was 120-220° C. and the heating time was 0.5-6 hours.

[0041] Based on the above preparation method, in step S5, the oxidation treatment method is a gas phase oxidation method or an electrochemical oxidation method;

[0042] in,

[0043] The gas phase oxidation method is specifically as follows: placing the catalyst powder in an oxygen-containing atmosphere for heating and oxidation, wherein the oxygen volume percentage is 0.01-1.0%, and a balance gas N2 is introduced, the oxidation temperature is 300-600°C, the heating rate of the oxidation temperature is 3-20°C / min, and the oxidation time is 1.0-4.0h;

[0044] The electrochemical oxidation method is specifically as follows: placing the catalyst powder in an inert atmosphere for heating oxidation, the oxidation temperature is 400-600°C, the oxidation temperature heating rate is 5-20°C / min, the oxidation time is 1.0-2.0h, the catalyst powder obtained after oxidation is coated on a glassy carbon electrode, immersed in O2-saturated 0.1M sulfuric acid, and potential cycled between 0-0.9Vvs RHE potential at a scanning rate of 10.0mV / s for 1 hour.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The carbon carrier of the present invention is pre-functionalized to introduce N and S heteroatoms, and the strong interaction between these atoms and precious metal atoms is utilized to ensure high stability between the catalyst active components and the carrier.

[0047] 2. The active components in the anode catalyst prepared by the present invention can form alloy clusters. At the same time, the surface species of the catalyst are regulated by heat treatment or electrochemical means, so that the precious metals are segregated to the surface and an oxide layer with the ability to block CO adsorption is formed on the outer layer. The physical barrier method is combined with the metal ligand effect. These two dual-functional mechanisms enhance the tolerance of the anode catalyst to CO and improve its CO anti-poisoning activity.

[0048] 3. In the process of generating the oxide barrier layer, the thickness of the oxide layer can be changed and precious metal alloy particles with controllable particle size can be formed by controlling the temperature and atmosphere in the post-treatment process and the ratio of the added Pt and Ru precursors, thereby regulating the thickness of the oxide layer, avoiding an excessively thick oxide layer that hinders the contact between the reactant molecules and the active sites, and ensuring the catalytic efficiency of the anode catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0050] Figure 1 TEM image of the catalyst (PtRu@t-RuO2 / C-(NH3)) prepared in Example 1, wherein the resolution is 10 nm;

[0051] Figure 2 TEM image of the catalyst (PtRu@t-RuO2 / C-(NH3)) prepared in Example 1, wherein the resolution is 50 nm;

[0052] Figure 3 XRD test patterns of the catalysts prepared in Examples 1, 4 and Comparative Example 4;

[0053] Figure 4 The XRD test patterns of the catalysts prepared in Comparative Examples 1 to 3;

[0054] Figure 5 CO dissolution curves of the catalysts prepared in Example 1 and Example 4 and Comparative Examples 1 to 3;

[0055] Figure 6 The current density-cell voltage curve of the catalyst prepared in Example 1 tested at the anode side of the membrane electrode in pure H2 and 1.0% CO / H2;

[0056] Figure 7 The current density-cell voltage curve of the catalyst prepared in Example 4 tested at the anode side of the membrane electrode in pure H2 and 1.0% CO / H2;

[0057] Figure 8 This is the constant current variation curve of the catalyst prepared in Example 4 when 1.0% CO / H2 was introduced into the anode side of the membrane electrode. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0059] The first embodiment of the present invention provides an anode catalyst resistant to CO poisoning, which is composed of a carbon carrier and precious metals and their oxide nanoclusters loaded on the carbon carrier, wherein the loading amount of the precious metals in the precious metals and their oxide nanoclusters is 25 to 75 wt% of the total loading amount of the anode catalyst; wherein the precious metals are ruthenium and platinum, and the weight ratio of ruthenium to platinum is 1 to 5:1.

[0060] In a specific implementation, the carbon carrier is an atom-doped carbon carrier;

[0061] The atoms doped in the atom-doped carbon carrier are nitrogen atoms and / or sulfur atoms;

[0062] The total doping amount of the nitrogen atoms and / or sulfur atoms is 1.8-2.2% of the weight of the carbon carrier.

[0063] As a specific implementation manner, the total doping amount of the nitrogen atoms and / or sulfur atoms is 2.0% of the weight of the carbon carrier.

[0064] In a specific implementation, the nanoparticle size of the noble metal and its oxide nanoclusters is 2.5 to 5.0 nm.

[0065] The second embodiment of the present invention provides a method for preparing an anode catalyst resistant to CO poisoning, which is used to prepare the above-mentioned anode catalyst. The preparation method comprises the following steps S1 to S5:

[0066] S1: Take 0.1-1.0 g of carbon carrier and add it into the solvent and shear for 30 minutes to obtain a uniformly dispersed slurry.

[0067] In this step, the shear rate is 8000-12000 rpm, and the solvent is any one of ethylene glycol, propylene glycol, glycerol, diethylene glycol, butylene glycol, diethylene glycol, triethylene glycol, or a mixture of any two or more thereof.

[0068] In a specific implementation, the carbon carrier is prepared by the following method:

[0069] S11: taking a common carbon carrier and adding heteroatoms by gas phase assistance to obtain the carbon carrier functionalized with heteroatoms.

[0070] In this step, the active heteroatoms generated by the decomposition of the nitrogen source or the sulfur source are assisted by the gas phase to react with the functional groups on the carbon surface, thereby obtaining the carbon carrier functionalized with heteroatoms.

[0071] In a specific implementation, the common carbon carrier is one of carbon black, activated carbon, graphite carbon, carbon nanotubes, graphene, and mesoporous carbon, or a mixture of any two or more thereof.

[0072] The specific steps of the gas phase assisted method are:

[0073] S111 places ordinary carbon carriers in a closed environment;

[0074] S112 introducing a gas containing a nitrogen source and / or a sulfur source into a closed environment;

[0075] S113 heat-treats the common carbon carrier at a temperature of 300 to 600°C, wherein the heating rate of the heat treatment is 5 to 20°C / min and the duration is 30 to 180 min.

[0076] In a specific implementation, the nitrogen source-containing gas may be NH3 or C2H8N2 / N2; the sulfur source-containing gas may be H2S, CS2 / N2, or Na2S / N2.

[0077] In a specific implementation, the gas inlet flow rate is 50.0 mL / min.

[0078] In a specific implementation, after the gas phase assistance is completed, 200.0 mL / min of H2 is introduced to purge the carbon carrier to cool it to room temperature for subsequent use.

[0079] In specific implementation, the common carbon carrier used in step S11 further includes a pretreatment step, and the pretreatment step includes:

[0080] S110 Weigh 0.1-1.0g of common carbon carrier, add 5.0-50mL of inorganic acid solution, heat and stir, wash with hot water until neutral, and then vacuum dry.

[0081] In the specific implementation, the inorganic acid in the pretreated inorganic acid solution is one of hydrochloric acid, nitric acid, sulfuric acid, acetic acid or a mixture of any two or more substances, the volume concentration of the inorganic acid solution is 30-80%, the heating and stirring temperature is 50-80°C, the stirring time is 1.0-4.0h, the drying temperature is 60-100°C, and the drying time is 12.0-48.0h.

[0082] S2: Mix the slurry with a noble metal ruthenium precursor solution, then add 1.0 to 10.0 mL of an inorganic base with a concentration of 0.1 to 2.0 mol / L for heating reaction, and then add a noble metal platinum precursor solution for heating reaction after cooling; wherein the ruthenium content in the noble metal ruthenium precursor is 0.2 to 2.0 g, and the platinum content in the noble metal platinum precursor is 0.1 to 1.0 g.

[0083] In this step, the purpose of adding inorganic base is that the alkalinity can improve the stability of the oxidation product of the solvent during the reaction, thereby controlling the particle size of the precious metal particles; and the purpose of adding inorganic acid is to adjust the zeta potential so that the nano-metal particles can be better loaded on the carbon carrier.

[0084] In a specific implementation, after adding an inorganic base for heating reaction, the temperature is lowered to 80° C. and then a noble metal platinum precursor solution is added for heating reaction.

[0085] In a specific implementation, in the noble metal ruthenium precursor solution, the noble metal ruthenium precursor is one of ruthenium trichloride, ruthenium acetylacetonate, ammonium hexachlororuthenate, hydrated potassium pentachlororuthenate, or a mixture of any two or more thereof;

[0086] In the noble metal platinum precursor solution, the noble metal platinum precursor is one of chloroplatinic acid, platinum chloride, platinum nitrate, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, sodium chloroplatinite, or a mixture of any two or more thereof;

[0087] The inorganic base is one of sodium carbonate, sodium hydroxide, potassium hydroxide, potassium carbonate, or a mixture of any two or more thereof;

[0088] The two heating reactions are both carried out under an inert gas (nitrogen, argon or helium) atmosphere, wherein the heating temperature is 120-220° C. and the heating time is 0.5-6 hours.

[0089] S4: adding water to the slurry after the stirring reaction, filtering and washing, and vacuum drying. The vacuum drying temperature is 60-100° C. and the processing time is 12.0-48.0 hours to obtain catalyst powder.

[0090] S5: subjecting the catalyst powder to oxidation treatment to obtain the anode catalyst.

[0091] In a specific implementation, the oxidation treatment method is a gas phase oxidation method or an electrochemical oxidation method;

[0092] in,

[0093] The gas phase oxidation method is specifically:

[0094] The catalyst powder is placed in an oxygen-containing atmosphere for heating oxidation, wherein the volume percentage of oxygen is 0.01-1.0%, and a balance gas N2 is introduced, the oxidation temperature is 300-600°C, the heating rate of the oxidation temperature is 3-20°C / min, and the oxidation time is 1.0-4.0h;

[0095] In a specific implementation, the heating rate of the oxidation temperature is 3-5°C / min.

[0096] The electrochemical oxidation method is specifically:

[0097] The catalyst powder is placed in an inert atmosphere for heating oxidation, the oxidation temperature is 400-600°C, the heating rate of the oxidation temperature is 5-20°C / min, and the oxidation time is 1.0-2.0h. The catalyst powder obtained after oxidation is coated on a glassy carbon electrode (GC, φ=5mm), immersed in O2-saturated 0.1M sulfuric acid, and potential cycled between 0-0.9Vvs RHE potential at a scanning rate of 10.0mV / s for 1 hour.

[0098] In this step, the precious metals are segregated to the catalyst surface and the carbon carrier surface through oxidation treatment, and a specific metal oxide layer is formed after oxidation, which weakens CO adsorption and improves the anti-poisoning performance of the catalyst.

[0099] In summary, the anode catalyst resistant to CO poisoning and the preparation method thereof of the present embodiment pre-treats the carbon carrier by utilizing the strong interaction characteristics between heteroatoms and precious metals. The carrier has a strong interaction force with the precious metal active components, so that the active components of the catalyst and the carrier have a high stability. At the same time, the preparation of the PtRu alloy is completed in the same container at one time (one-pot method), so that the alloying degree of the catalyst is high. At the same time, the thickness of the Ru oxide barrier layer can be changed by adjusting the Pt / Ru addition ratio, and the barrier layer thickness of the barrier layer can be effectively controlled. During the preparation, the catalyst is subjected to a single oxidation treatment to form A layer of oxide blocks CO adsorption on the outside, and this layer of oxide allows the reactant H2 to pass freely, while PtRu particles with a high degree of alloying are formed in the inner layer of the catalyst. Due to the existence of the metal ligand effect, the bonding of CO on the surface of the precious metal can be weakened. At the same time, the hydroxyl radicals generated can oxidize and remove the adsorbed CO, which can effectively improve the CO tolerance. The prepared anode catalyst has a dual functional mechanism of physical blocking of CO adsorption by the outer layer and catalytic oxidation of CO removal by the inner layer. It has excellent resistance to CO poisoning and catalytic hydrogen oxidation activity, and due to the strong binding ability of the precious metal and the carrier, it also has excellent stability.

[0100] For better understanding and implementation of the present invention, the present invention is further explained and illustrated below in conjunction with specific embodiments.

[0101] Example 1

[0102] A method for preparing an anode catalyst resistant to CO poisoning comprises the following steps:

[0103] 1. Carbon carrier pretreatment: Weigh 0.15 g of Japanese Lion Ketjen Black EC300J superconducting carbon black (abbreviated as KB300, the same below) and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% (volume concentration, the same below) nitric acid solution and stir for 2.0 h. After the end, filter it immediately and rinse it with an appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the filtered sample and place it under vacuum at 80°C for 24.0 h.

[0104] 2. Nitrogen doping: Weigh the sample obtained in the previous step into a quartz boat, place the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 400°C, the heating rate to 5°C / min, and maintain the temperature for 1.0h. During the heating process, introduce 50.0mL / min of N2. After reaching the set temperature, switch to 50.0mL / min of high-purity NH3 atmosphere. After the treatment is completed, turn off the NH3 source, introduce 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a nitrogen content of 2.0%.

[0105] 3. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g of Ru atoms) and 0.1 g of a carbon carrier with a nitrogen content of 2.0% were added to a 1 L flask, and 6.0 mL of a 0.1 mol / L NaOH solution (the solvent is diethylene glycol, the same below) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180° C. for 2.0 h, and after the reaction was completed, the temperature was lowered to about 80° C. (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g of Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL, and the reaction temperature was set at 150° C. for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and then a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60° C. for 1.0 h.

[0106] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0107] 5. Catalyst heat treatment: Weigh the sample into a quartz boat, place the quartz boat into a slide rail tube furnace, and introduce a 0.1% by volume O2 / N2 atmosphere at a flow rate of 50 mL / min into the tube furnace for gas replacement for 2.0 hours. When the furnace temperature reaches the set temperature of 550°C, control the quartz boat to enter the slide rail tube furnace body and heat treat for 2.0 hours.

[0108] In this embodiment, the carrier is KB300 modified with ammonia as the nitrogen source, the active component is a metal active species composed of a platinum-ruthenium alloy as a core and ruthenium oxide (heat treated) as a shell. The prepared catalyst is recorded as PtRu@t-RuO2 / C-(NH3), and the precious metal content is 75.0%.

[0109] Example 2

[0110] A method for preparing an anode catalyst resistant to CO poisoning comprises the following steps:

[0111] 1. Carbon carrier pretreatment: Weigh 0.15 g of KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. Filter immediately after the end and rinse with appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the filtered sample and place it in a vacuum dryer at 80°C for 24.0 h.

[0112] 2. Nitrogen doping: Weigh the sample obtained in the previous step into a quartz boat, place the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 600°C, the heating rate to 10°C / min, maintain the temperature for 1.0h, and introduce 50.0mL / min of N2 during the heating process; after reaching the set temperature, switch to 50.0mL / min of C2H8N2 / N2 atmosphere (C2H8N2 solution and H2O are prepared in a molar ratio of 2:3, added to a washing bottle, and bubbled with N2). After the treatment, turn off the nitrogen source atmosphere, introduce 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a nitrogen content of 2.0%.

[0113] 3. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g of Ru atoms) and 0.1 g of a carbon carrier with a nitrogen content of 2.0% were added to a 1 L flask, and a certain amount of 0.1 mol / L NaOH solution (6.0 mL) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180° C. for 2.0 h, and after the reaction was completed, the temperature was lowered to about 80° C. (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g of Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL, and the reaction temperature was set at 150° C. and reacted for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60° C. for 1.0 h.

[0114] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0115] 5. Catalyst heat treatment: Weigh 0.1g of sample into a quartz boat, place the quartz boat into a slide rail tube furnace, and introduce 0.1% O2 / N2 atmosphere at a flow rate of 50mL / min into the tube furnace for gas replacement for 2.0h. When the furnace temperature reaches the set temperature of 550℃, control the quartz boat to enter the slide rail tube furnace body and heat treat for 2.0h.

[0116] In this embodiment, the carrier is KB300 modified with ethylenediamine as the nitrogen source, and the active component is a metal active species composed of a platinum-ruthenium alloy as a core and ruthenium oxide (heat treated) as a shell. The prepared catalyst is recorded as PtRu@t-RuO2 / C-(C2H8N2), and the precious metal content is 75.0%.

[0117] Example 3

[0118] A method for preparing an anode catalyst resistant to CO poisoning comprises the following steps:

[0119] 1. Carbon carrier pretreatment: Weigh 0.15 g of KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. Filter immediately after the end and rinse with appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the filtered sample and place it in a vacuum dryer at 80°C for 24.0 h.

[0120] 2. Nitrogen doping: Weigh the sample obtained in the previous step into a quartz boat, place the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 400°C, the heating rate to 5°C / min, and maintain the temperature for 1.0h. During the heating process, introduce 50.0mL / min of N2. After reaching the set temperature, switch to 50.0mL / min of high-purity NH3 atmosphere. After the treatment is completed, turn off the NH3 source, introduce 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a nitrogen content of 2.0%.

[0121] 3. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g of Ru atoms) and 0.1 g of a carbon carrier with a nitrogen content of 2.0% were added to a 1 L flask, and a certain amount of 0.1 mol / L NaOH solution (6.0 mL) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180° C. for 2.0 h, and after the reaction was completed, the temperature was lowered to about 80° C. (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g of Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL, and the reaction temperature was set at 150° C. for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60° C. for 1.0 h.

[0122] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0123] 5. Catalyst oxidation treatment: Weigh 10.0 mg of the catalyst obtained in the previous step, add 7.0 mL of ultrapure water, 50 μL of perfluorosulfonic acid resin solution and 3.0 mL of isopropanol in sequence, then mix by ultrasonication at -5.0°C for 10 min, drop-coat on a glassy carbon electrode (GC, φ=5 mm), spin-dry at 500 rpm, and then immerse in O2-saturated 0.1 M sulfuric acid, and perform potential cycling between 0-0.9 V vs RHE at a scan rate of 10.0 mV / s for 1 hour.

[0124] In this Example 3, the carrier is KB300 modified with ammonia as the nitrogen source, the active component is a metal active species composed of a platinum-ruthenium alloy as a core and ruthenium oxide (electrochemical oxidation) as a shell, and the prepared catalyst is recorded as PtRu@e-RuO2 / C-(NH3), and the precious metal content is 75.0%.

[0125] Example 4

[0126] A method for preparing an anode catalyst resistant to CO poisoning comprises the following steps:

[0127] 1. Carbon carrier pretreatment: Weigh 0.15 g of KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. Filter immediately after the end and rinse with appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the filtered sample and place it in a vacuum dryer at 80°C for 24.0 h.

[0128] 2. Sulfur doping: Weigh the sample obtained in the previous step into a quartz boat, place the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 600°C, the heating rate to 10°C / min, and maintain the temperature for 1.0h. During the heating process, 50.0mL / min of N2 was introduced. After reaching the set temperature, switch to 50.0mL / min of CS2 / N2 atmosphere (CS2 solution is added to a washing bottle, placed in an ice bath at -20°C, and bubbled with N2). After the treatment is completed, turn off the sulfur source atmosphere, introduce 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a sulfur content of 2.0%.

[0129] 3. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g of Ru atoms) and 0.1 g of a carbon carrier with a sulfur content of 2.0% were added to a 1 L flask, and a certain amount of 0.1 mol / L NaOH solution (6.0 mL) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180° C. for 2.0 h, and after the reaction was completed, the temperature was lowered to about 80° C. (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g of Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL, and the reaction temperature was set at 150° C. for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60° C. for 1.0 h.

[0130] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0131] 5. Catalyst heat treatment: Weigh the sample into a quartz boat, place the quartz boat into a slide rail tube furnace, and introduce a 0.1% volume percentage O2 / N2 atmosphere at a flow rate of 50 mL / min into the tube furnace for gas replacement for 2.0 hours. When the furnace body temperature reaches the set temperature of 550°C, control the quartz boat to enter the slide rail tube furnace body and heat treat for 2.0 hours.

[0132] In this embodiment, the carrier is KB300 modified with carbon disulfide as the sulfur source, the active component is a metal active species composed of a platinum-ruthenium alloy as a core and ruthenium oxide (heat treated) as a shell. The prepared catalyst is recorded as PtRu@t-RuO2 / C-(CS2), and the precious metal content is 75.0%.

[0133] Example 5

[0134] A method for preparing an anode catalyst resistant to CO poisoning comprises the following steps:

[0135] 1. Carbon carrier pretreatment: Weigh 0.15 g of KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. Filter immediately after the end and rinse with appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the filtered sample and place it in a vacuum dryer at 80°C for 24.0 h.

[0136] 2. Sulfur doping: Weigh the sample obtained in the previous step into a quartz boat, put the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 600°C, the heating rate to 10°C / min, maintain the temperature for 1.0h, and pass 50.0mL / min of N2 during the heating process. After reaching the set temperature, switch to 50.0mL / min of H2S atmosphere. After the treatment is completed, turn off the sulfur source atmosphere, pass 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a sulfur content of 2.0%.

[0137] 3. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g of Ru atoms) and 0.1 g of a carbon carrier with a sulfur content of 2.0% were added to a 1 L flask, and a certain amount of 0.1 mol / L NaOH solution (6.0 mL) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180° C. for 2.0 h, and after the reaction was completed, the temperature was lowered to about 80° C. (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g of Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL, and the reaction temperature was set at 150° C. for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60° C. for 1.0 h.

[0138] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0139] 5. Catalyst heat treatment: Weigh the sample into a quartz boat, place the quartz boat into a slide rail tube furnace, and introduce a 0.1% volume percentage O2 / N2 atmosphere at a flow rate of 50 mL / min into the tube furnace for gas replacement for 2.0 hours. When the furnace body temperature reaches the set temperature of 550°C, control the quartz boat to enter the slide rail tube furnace body and heat treat for 2.0 hours.

[0140] In this embodiment, the carrier is KB300 modified with hydrogen sulfide as the sulfur source, and the active component is a metal active species composed of a platinum-ruthenium alloy as a core and ruthenium oxide (heat treated) as a shell. The prepared catalyst is recorded as PtRu@t-RuO2 / C-(H2S), and the precious metal content is 75.0%.

[0141] Example 6

[0142] A method for preparing an anode catalyst resistant to CO poisoning comprises the following steps:

[0143] 1. Carbon carrier pretreatment: Weigh 0.15 g of KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. Filter immediately after the end and rinse with appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the filtered sample and place it in a vacuum dryer at 80°C for 24.0 h.

[0144] 2. Sulfur doping: weigh the sample obtained in the previous step into a quartz boat, put the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 600°C, the heating rate to 10°C / min, maintain the temperature for 1.0h, and pass 50.0mL / min of N2 during the heating process. After reaching the set temperature, switch to 50.0mL / min of CS2 / N2 atmosphere (CS2 solution is added to a washing bottle, placed in an ice bath at -20°C, and bubbled with N2). After the treatment is completed, turn off the sulfur source atmosphere, pass 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a sulfur content of 2.0%.

[0145] 3. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g of Ru atoms) and 0.1 g of a carbon carrier with a sulfur content of 2.0% were added to a 1 L flask, and a certain amount of 0.1 mol / L NaOH solution (6.0 mL) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180° C. for 2.0 h, and after the reaction was completed, the temperature was lowered to about 80° C. (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g of Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL, and the reaction temperature was set at 150° C. for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60° C. for 1.0 h.

[0146] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0147] 5. Catalyst oxidation treatment: Weigh 10.0 mg of the catalyst obtained in the previous step, add 7.0 mL of ultrapure water, 50 μL of perfluorosulfonic acid resin solution and 3.0 mL of isopropanol in sequence, then mix by ultrasonication at -5.0°C for 10 min, drop-coat on a glassy carbon electrode (GC, φ=5 mm), spin-dry at 500 rpm, and then immerse in O2-saturated 0.1 M sulfuric acid, and perform potential cycling between 0-0.9 V vs RHE at a scan rate of 10.0 mV / s for 1 hour.

[0148] In this embodiment, the carrier is KB300 modified with carbon disulfide as the sulfur source, the active component is a metal active species composed of a platinum-ruthenium alloy as a core and ruthenium oxide (electrochemical oxidation) as a shell, and the prepared catalyst is recorded as PtRu@e-RuO2 / C-(CS2), and the precious metal content is 75.0%.

[0149] Comparative Example 1

[0150] This comparative example adopts a one-pot method to synthesize the catalyst, does not adopt a carrier modification process and a catalyst secondary heat treatment oxidation process, and the carrier is not doped with heteroatoms.

[0151] This comparative example is specifically a method for preparing a catalyst, comprising the following steps:

[0152] 1. Carbon carrier pretreatment: Weigh 0.15 g of carbon carrier KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. After the end, filter it immediately and rinse it with an appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the catalyst and place it at 80°C under vacuum for 24.0 h.

[0153] 2. Catalyst synthesis: ruthenium acetylacetonate solution (containing 0.2 g Ru atoms) and 0.1 g carrier KB300 were added to a 1 L flask, and a certain amount of 0.1 mol / L NaOH solution (6.0 mL) was added, and diethylene glycol was added to control the total volume to 50 mL; the temperature of the oil bath was adjusted to react at 180°C for 2.0 h. After the reaction was completed, the temperature was lowered to about 80°C (stable for 10 min), and chloroplatinic acid solution (containing 0.1 g Pt atoms) and a certain amount of 0.1 mol / L NaOH solution were added, and a certain amount of diethylene glycol solution was added to make the feeding volume 100 mL. The reaction temperature was set at 150°C for 2.0 h; after the reaction was completed, an equal volume of deionized water was added, and a certain concentration of HCl solution was added, the pH was adjusted to 4.0, and stirring was maintained at 60°C for 1.0 h.

[0154] 3. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0155] In this comparative example, the carrier is KB300, the active component is a platinum-ruthenium alloy species, the prepared catalyst is recorded as PtRu / C, and the precious metal content is 75.0%.

[0156] Comparative Example 2

[0157] This comparative example adopts a one-pot method to synthesize the catalyst, adopts a carrier nitrogen modification process, and does not adopt a catalyst secondary heat treatment oxidation process.

[0158] This comparative example is specifically a method for preparing a catalyst, comprising the following steps:

[0159] 1. Carbon carrier pretreatment: Weigh 0.15 g of carbon carrier KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. After the end, filter it immediately and rinse it with an appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the catalyst and place it at 80°C under vacuum for 24.0 h.

[0160] 2. Nitrogen doping: Weigh the sample obtained in the previous step into a quartz boat, place the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 400°C, the heating rate to 5°C / min, and maintain the temperature for 1.0h. During the heating process, introduce 50.0mL / min of N2. After reaching the set temperature, switch to 50.0mL / min of high-purity NH3 atmosphere. After the treatment is completed, turn off the NH3 source, introduce 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a nitrogen content of 2.0%.

[0161] 3. Catalyst synthesis: add ruthenium acetylacetonate solution (containing 0.2g Ru atom) and 0.1g carrier into a 1L flask, add a certain amount of 0.1mol / L NaOH solution (6.0mL) at the same time, and then add diethylene glycol to control the total volume to 50mL; adjust the temperature of the oil bath to react at 180°C for 2.0h, after the reaction is completed, wait for the temperature to drop to about 80°C (stable for 10min), add chloroplatinic acid solution (containing 0.1g Pt atom) and a certain amount of 0.1mol / L NaOH solution, and then add a certain amount of diethylene glycol solution to make the feeding volume 100mL, set the reaction temperature to 150°C for 2.0h; after the reaction is completed, add an equal volume of deionized water, then add a certain concentration of HCl solution, adjust the pH to 4.0, and keep stirring at 60°C for 1.0h.

[0162] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0163] In this comparative example, the carrier is KB300 modified with ammonia as the nitrogen source, the active component is a platinum-ruthenium alloy species, the prepared catalyst is denoted as PtRu / C-(NH3), and the precious metal content is 75.0%.

[0164] Comparative Example 3

[0165] This comparative example adopts a one-pot method to synthesize the catalyst, adopts a carrier nitrogen modification process, and does not adopt a catalyst secondary heat treatment oxidation process.

[0166] This comparative example is specifically a method for preparing a catalyst, comprising the following steps:

[0167] 1. Carbon carrier pretreatment: Weigh 0.15 g of carbon carrier KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. After the end, filter it immediately and rinse it with an appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the catalyst and place it at 80°C under vacuum for 24.0 h.

[0168] 2. Sulfur doping: weigh the sample after drying in the previous step into a quartz boat, put the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 600°C, the heating rate to 10°C / min, maintain the temperature for 1.0h, and pass 50.0mL / min of N2 during the heating process. After reaching the set temperature, switch to 50.0mL / min of CS2 / N2 atmosphere (CS2 solution is added to a washing bottle, placed in an ice bath at -20°C, and bubbled with N2). After the treatment is completed, turn off the sulfur source atmosphere, pass 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a sulfur content of 2.0%.

[0169] 3. Catalyst synthesis: add ruthenium acetylacetonate solution (containing 0.2g Ru atom) and 0.1g carrier into a 1L flask, add a certain amount of 0.1mol / L NaOH solution (6.0mL) at the same time, and then add diethylene glycol to control the total volume to 50mL; adjust the temperature of the oil bath to react at 180°C for 2.0h, after the reaction is completed, wait for the temperature to drop to about 80°C (stable for 10min), add chloroplatinic acid solution (containing 0.1g Pt atom) and a certain amount of 0.1mol / L NaOH solution, and then add a certain amount of diethylene glycol solution to make the feeding volume 100mL, set the reaction temperature to 150°C for 2.0h; after the reaction is completed, add an equal volume of deionized water, then add a certain concentration of HCl solution, adjust the pH to 4.0, and keep stirring at 60°C for 1.0h.

[0170] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0171] In this comparative example, the carrier is KB300 modified with carbon disulfide as the sulfur source, the active component is a platinum-ruthenium alloy species, the prepared catalyst is denoted as PtRu / C-(CS2), and the noble metal content is 75.0%.

[0172] Comparative Example 4

[0173] This comparative example adopts a one-pot method to synthesize the catalyst, adopts a carrier nitrogen modification process, changes the ratio of platinum and ruthenium incorporated to form an alloy, and then adopts a catalyst secondary heat treatment oxidation process to construct a CO barrier layer outside the catalyst.

[0174] This comparative example is specifically a method for preparing a catalyst, comprising the following steps:

[0175] 1. Carbon carrier pretreatment: Weigh 0.15 g of carbon carrier KB300 and place it in a round-bottom flask, heat it to 70°C, then add 10 mL of 70% nitric acid solution and stir for 2.0 h. After the end, filter it immediately and rinse it with an appropriate amount of hot water until the pH of the filtrate becomes neutral. Take out the catalyst and place it at 80°C under vacuum for 24.0 h.

[0176] 2. Nitrogen doping: Weigh the sample obtained in the previous step into a quartz boat, place the quartz boat into a slide rail tube furnace, and then set the heat treatment temperature to 400°C, the heating rate to 5°C / min, and maintain the temperature for 1.0h. During the heating process, introduce 50.0mL / min of N2. After reaching the set temperature, switch to 50.0mL / min of high-purity NH3 atmosphere. After the treatment is completed, turn off the NH3 source, introduce 200.0mL / min of N2 to purge and cool to room temperature to obtain a carbon carrier with a nitrogen content of 2.0%.

[0177] 3. Catalyst synthesis: add ruthenium acetylacetonate solution (containing 0.1g Ru atoms) and 0.1g carrier into a 1L flask, add a certain amount of 0.1mol / L NaOH solution (6.0mL), and then add diethylene glycol to control the total volume to 50mL; adjust the temperature of the oil bath to react at 180°C for 2.0h, after the reaction is completed, wait for the temperature to drop to about 80°C (stable for 10min), add chloroplatinic acid solution (containing 0.1g Pt atoms) and a certain amount of 0.1mol / L NaOH solution, and then add a certain amount of diethylene glycol solution to make the feeding volume 100mL, set the reaction temperature to 150°C for 2.0h; after the reaction is completed, add an equal volume of deionized water, then add a certain concentration of HCl solution, adjust the pH to 4.0, and keep stirring at 60°C for 1.0h.

[0178] 4. Catalyst drying: The above materials were filtered and washed, and the powder samples were dried in a vacuum oven at 70°C for 12.0 h.

[0179] 5. Catalyst heat treatment: Weigh the sample into a quartz boat, place the quartz boat into a slide rail tube furnace, and introduce a 0.1% volume percentage O2 / N2 atmosphere at a flow rate of 50 mL / min into the tube furnace for gas replacement for 2.0 hours. When the furnace body temperature reaches the set temperature of 550°C, control the quartz boat to enter the slide rail tube furnace body and heat treat for 2.0 hours.

[0180] In this comparative example, the carrier is KB300 modified with ammonia as the nitrogen source, the active component is a metal active species composed of a platinum-ruthenium alloy as a core (wherein the platinum content is 0.1 g, and the ruthenium content is reduced from 0.2 g to 0.1 g) and ruthenium oxide (heat treated) as a shell. The prepared catalyst is recorded as PtRu@t-RuO2 / C-(NH3)-LC, the precious metal content is 50.0%, and the platinum-ruthenium ratio is 1:1.

[0181] The following comparison is made in combination with Examples 1-6 and Comparative Examples 1-4:

[0182] Figure 1 TEM image of the catalyst (PtRu@t-RuO2 / C-(NH3)) prepared in Example 1, wherein the resolution is 10 nm; Figure 2 This is a TEM image of the catalyst (PtRu@t-RuO2 / C-(NH3)) prepared in Example 1, with a resolution of 50nm. Figure 1 and Figure 2 The microscopic morphology of the catalyst (PtRu@t-RuO2 / C-(NH3)) can be seen. The catalyst is uniform in size, with a particle size of about 2.50 nm, and a clear shell boundary can be seen under high magnification, indicating that the desired CO-poisoning-resistant catalyst can be synthesized according to the preparation method of Example 1.

[0183] The catalysts prepared in Example 1, Example 4 and Comparative Examples 1 to 3 were subjected to a CO dissolution test, and the test contents were specifically as follows:

[0184] The catalyst powders prepared in Example 1, Example 4 and Comparative Examples 1 to 3 were weighed into a 20 mL glass bottle, a certain proportion of ultrapure water and isopropanol were added, ultrasonic dispersion was performed for 7 min, a perfluorosulfonic acid polymer solution (Nafion) (concentration 5 wt%) was added dropwise, ultrasonic cleaning was performed for 2 min, 6.5 μL of catalyst slurry (ink) was measured with a pipette, and it was dropped on a glassy carbon disk electrode at one time and rotated to dry. In the test, a saturated calomel electrode was used as the reference electrode, a graphite electrode was used as the counter electrode, a three-electrode test system was built, and the electrolyte was 0.1M HClO4 solution. The reference electrode was calibrated first, and then the working electrode was activated at 0.05V / s with the scanning number of 30 circles. 5% CO / N2 was introduced into the electrolytic cell, and the constant current test mode was selected. Carbon monoxide was adsorbed at a potential of 0.05V vs.RHE for 20 minutes and then paused. The CO gas was quickly switched to nitrogen (maintained at 0.05V vs.RHE) and continued to be purged for 10 minutes to remove CO in the electrolyte. Then, according to the cyclic voltammetry test procedure, 3 circles were scanned to obtain the CO dissolution curve. After data processing and calculation, the electrochemical active area measured under the CO dissolution method can be obtained.

[0185] The specific data after the test are shown in Table 1 below:

[0186]

[0187] Table 1: Electrochemical performance data of catalysts prepared in Examples 1-6 and Comparative Examples 1-4

[0188] at the same time, Figure 3 XRD test patterns of the catalysts prepared in Examples 1, 4 and Comparative Example 4; Figure 4 The XRD test patterns of the catalysts prepared in Comparative Examples 1 to 3; Figure 5 CO dissolution curves of the catalysts prepared in Example 1 and Example 4 and Comparative Examples 1 to 3.

[0189] Combined with Table 1 and Figure 3-5 Combined, we can see that:

[0190] The catalysts prepared in Examples 1-6, because they were all synthesized according to the dual mechanism of outer layer blocking and inner layer alloying, showed better electrochemical activity in the CO dissolution test compared with Comparative Examples 1-3, indicating that they have better catalytic performance under half-cell conditions. Figure 5The curve changes of the CO dissolution experiment show that the oxidation potential of the catalysts prepared in Examples 1 and 4 is not significantly increased compared with Comparative Examples 1 to 3. This is because the catalyst adopts a bifunctional mechanism, and the oxidation potential shown by the CO oxidation mechanism cannot be used alone to compare the anti-CO poisoning ability. This can be seen from Figure 3 and Figure 4 The XRD test images are explained. Figure 3 The catalyst prepared in the corresponding example has only the peak signal of RuO2 because the alloy is wrapped by the shell layer; Figure 4 The comparative catalyst in the example has no shell layer and only exhibits alloy diffraction peaks.

[0191] Compared with Example 1, the ratio of precious metal platinum to ruthenium in the catalyst was adjusted in Comparative Example 4 (from 1:2 to 1:1), which would significantly affect the thickness and particle size of the barrier layer and the PtRu alloy. Therefore, the electrochemical active area measured by the CO dissolution method was lower than that of Example 1, and the CO oxidation ability was poor. Figure 3 It can be seen that the XRD diffraction signal of the catalyst PtRu / C-(NH3)-LC at a ratio of 1:1 shows a wider peak signal, which is compared with Example 1, indicating that the catalyst particle size formed is smaller, that is, the barrier layer is thinner.

[0192] At the same time, by comparing Examples 1 to 3 with Examples 4 to 6 in Table 1, it can be seen that the electrochemical activity of the catalyst doped with sulfur is always better than that of the catalyst doped with nitrogen. This is because the sulfur atom has a stronger binding ability with the precious metal, which enables the barrier layer RuO2 generated after oxidation to be strongly bound to the carbon carrier. This strong metal-carrier interaction effect is conducive to the catalyst exhibiting excellent anti-CO poisoning performance.

[0193] Figure 6 The current density-cell voltage curve of the catalyst prepared in Example 1 tested at the anode side of the membrane electrode in pure H2 and 1.0% CO / H2; Figure 7 The current density-cell voltage curve of the catalyst prepared in Example 4 tested at the anode side of the membrane electrode in pure H2 and 1.0% CO / H2; Figure 8 This is the constant current variation curve of the catalyst prepared in Example 4 when 1.0% CO / H2 was introduced into the anode side of the membrane electrode.

[0194] Combination Figure 6-Figure 8 It can be seen that:

[0195] When tested under pure hydrogen, the catalysts prepared in Examples 1 and 4 have comparable performances, but the polarization curves under 1.0% CO / H2 flow at 2.0 A / cm 2 The voltage losses under 3.8% and 5.6% were respectively, both showing excellent resistance to CO poisoning.

[0196] The catalyst prepared in Example 4 has a tolerance to 1.0% CO / H2 under constant current density test, and the voltage loss is about 15% within 350 minutes. However, in Comparative Example 1, which does not adopt this preparation method, since there is no RuO2 blocking the outer layer of the catalyst, under the same CO concentration carrier, CO is adsorbed on the catalyst to occupy the Pt active site, affecting the hydrogen oxidation reaction, so the voltage loss reaches 80% within only 1.0 hour, the electrochemical performance is significantly reduced, and it is impossible to achieve resistance to CO poisoning.

[0197] and then:

[0198] Combination Figure 1 The obvious core-shell structure and Figure 3 The results of only assigning the shell RuO2 diffraction peak indicate that the pre-treatment method of sulfur / nitrogen atom-doped carbon carrier can induce the strong binding of the precious metal ruthenium with the carrier on the catalyst surface; when subjected to oxidation treatment, the outer ruthenium atoms will segregate to the surface to form an oxide barrier layer, and adjusting the platinum-ruthenium ratio can control the thickness of the outer barrier and the particle size of the PtRu alloy, thereby improving material transport and enhancing catalytic activity.

[0199] Comparison Table 1 Test Data and Figures 3 to 5 The characterization results show that the catalyst prepared in the example has the dual-function mechanism proposed by the present invention under the anode reaction containing carbon monoxide, that is, the outer oxide first blocks CO on the catalyst surface, but allows the reactant H2 to pass through, and then the active species catalyzes the anode reaction to generate protons; when high-concentration CO penetrates, the CO entering the inner layer will be combined with the hydroxyl radicals generated by the alloy species PtRu and catalytically converted into CO2. Figures 6 to 8 In the poisoning test results, the catalyst designed by the present invention exhibited significantly improved electrochemical activity and resistance to CO poisoning.

[0200] It can be seen from this that the CO poisoning-resistant anode catalyst involved in the present invention has a dual functional mechanism of outer layer physical blocking of CO adsorption and inner layer catalytic oxidation of CO removal, has excellent CO poisoning resistance and catalytic hydrogen oxidation activity, and due to the strong binding ability of the precious metal and the carrier, also has excellent stability.

[0201] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A CO-poisoning resistant anode catalyst, characterized in that: It is composed of a carbon carrier and a noble metal and its oxide nanoclusters loaded on the carbon carrier, wherein the loading amount of the noble metal in the noble metal and its oxide nanoclusters is 25-75wt% of the total loading amount of the anode catalyst; Wherein, the precious metals are ruthenium and platinum, and the weight ratio of ruthenium to platinum is 1 to 5:

1.

2. The anode catalyst according to claim 1, characterized in that The carbon carrier is an atom-doped carbon carrier; The atoms doped in the atom-doped carbon carrier are nitrogen atoms and / or sulfur atoms; The total doping amount of the nitrogen atoms and / or sulfur atoms is 1.8-2.2% of the weight of the carbon carrier.

3. The anode catalyst according to claim 1, characterized in that The particle size of the nanoparticles of the noble metal and its oxide nanocluster is 2.5-5.0 nm.

4. A method for preparing an anode catalyst resistant to CO poisoning, for preparing the anode catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: 0.1-1.0 g of carbon carrier is added into the solvent and sheared for 30 min to obtain a uniformly dispersed slurry; S2: mixing the slurry with a noble metal ruthenium precursor solution, adding 1.0-10.0 mL of an inorganic base with a concentration of 0.1-2.0 mol / L to carry out a heating reaction, and then adding a noble metal platinum precursor solution to carry out a heating reaction after cooling; wherein the content of ruthenium in the noble metal ruthenium precursor is 0.2-2.0 g, and the content of platinum in the noble metal platinum precursor is 0.1-1.0 g; S3: cooling the slurry after the heating reaction, adding deionized water, and then adding 1.0-20.0 mL of an inorganic acid solution with a concentration of 0.1-1.5 mol / L to carry out stirring reaction; wherein the reaction temperature of the stirring reaction is 60-100° C., and the stirring time is 1.0-3.0 h; S4: adding water to the slurry after the stirring reaction, filtering and washing, and vacuum drying, the vacuum drying temperature is 60-100° C., and the treatment time is 12.0-48.0 hours to obtain a catalyst powder; S5: subjecting the catalyst powder to oxidation treatment to obtain the anode catalyst.

5. The preparation method according to claim 4, characterized in that: The carbon carrier in step S1 is prepared by the following method: A common carbon carrier is doped with heteroatoms through gas phase assistance to obtain the carbon carrier functionalized with heteroatoms.

6. The preparation method according to claim 5, characterized in that: The common carbon carrier further comprises a pretreatment step, wherein the pretreatment step comprises: Weigh 0.1-1.0 g of common carbon carrier, add 5.0-50 mL of inorganic acid solution, heat and stir, wash with hot water until neutral and then vacuum dry.

7. The preparation method according to claim 4, 5 or 6, characterized in that: The common carbon carrier is one of carbon black, activated carbon, graphite carbon, carbon nanotubes, graphene, and mesoporous carbon, or a mixture of any two or more of the above substances.

8. The preparation method according to claim 5, characterized in that: The specific steps of the gas phase assistance are: Place the common carbon support in a closed environment; Passing a gas containing a nitrogen source and / or a sulfur source into a closed environment; The common carbon carrier is heat-treated at a temperature of 300 to 600° C., wherein the heating rate of the heat treatment is 5 to 20° C. / min and the duration is 30 to 180 min.

9. The preparation method according to claim 4, characterized in that: In the step S1, the shear rate is 8000-12000 rpm, and the solvent is any one of ethylene glycol, propylene glycol, glycerol, diethylene glycol, butylene glycol, diethylene glycol, triethylene glycol, or a mixture of any two or more thereof.

10. The preparation method according to claim 4, characterized in that: In step S2: In the noble metal ruthenium precursor solution, the noble metal ruthenium precursor is one of ruthenium trichloride, ruthenium acetylacetonate, ammonium hexachlororuthenate, hydrated potassium pentachlororuthenate, or a mixture of any two or more thereof; In the noble metal platinum precursor solution, the noble metal platinum precursor is one of chloroplatinic acid, platinum chloride, platinum nitrate, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, sodium chloroplatinite, or a mixture of any two or more thereof; The inorganic base is one of sodium carbonate, sodium hydroxide, potassium hydroxide, potassium carbonate, or a mixture of any two or more thereof; The heating reactions were both carried out under an inert gas atmosphere, wherein the heating temperature was 120-220° C. and the heating time was 0.5-6 hours.